PENERAPAN ALGORITMA K-MEANS CLUSTERING PADA ANALISIS POLA PENDAFTARAN CALON JAMAAH HAJI DI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI JAMBI - Hikmatul Ilmi; Novhirtamely Kahar (FORTECH (Journal of Information Technology), 2026)
This study aims to analyze the registration patterns of prospective hajj pilgrims at the Regional Office of the Ministry of Religious Affairs of Jambi Province using the K-Means Clustering algorithm. The main issue addressed is the high volume of hajj applicants each year without adequate pattern analysis, which complicates quota planning and pilgrim guidance. The dataset includes the number of hajj applicants per regency/city from 2018 to 2024, with attributes such as applicant count, age, and gender. The clustering process was carried out using K-Means with k = 3, resulting in three main clusters: high, medium, and low registration rates. The results show that Batanghari Regency and Jambi City belong to the high cluster, while Tebo and Sarolangun are in the low cluster. These findings provide better insights for policymakers in managing hajj quotas and improving outreach strategies.